PENGUATAN PROFIL PELAJAR PANCASILA PADA PEMBELAJARAN AGAMA ISLAM DI MADRASAH IBTIDAIYAH NEGERI 2 PAMEKASAN - Rofiki; Fathurrosyid (CV. Jendela Gagasan, 2025)
Strengthening the Pancasila Student Profile in Islamic education at madrasahs is an interesting educational phenomenon in the context of integrating Islamic values with national values. The implementation of the Pancasila Student Profile at madrasahs faces the challenge of balancing the development of religious character with national character in accordance with the values of Pancasila. Madrasahs have a strategic role in shaping students who not only have strong spiritual competence but are also capable of becoming Indonesian citizens with character. The integration of these two value systems requires a holistic and contextual learning approach to produce graduates with a complete Indonesian Muslim identity. This study aims to answer how the implementation of strengthening the Pancasila Student Profile in Islamic Education at State Elementary Madrasah 2 Pamekasan is carried out and what the results are. The research uses a qualitative method with a case study approach at MIN 2 Pamekasan. Data sources include Islamic religion teachers, students, the madrasah principal, and parents. Data collection techniques include in-depth interviews, participatory observation, and documentation. Data analysis uses data reduction, data presentation, and conclusion drawing with triangulation of sources. The research results indicate that the implementation was carried out through a holistic integrative approach with three stages: planning (integration of Pancasila values into the lesson plan), implementation (collaborative learning, contextual approach, and integration of global diversity), and evaluation (authentic assessment and behavioral observation). The implementation produced three positive impacts: improved understanding of religious and Pancasila values, development of character traits such as honesty, responsibility, and empathy, and enhanced ability to collaborate and appreciate differences, reflecting the success of the transformative Islamic education model.